Transforming growth factor‐β(1) elicits Nrf2‐mediated antioxidant responses in aortic smooth muscle cells - Churchman, Adrian T. (J Cell Mol Med, 2009)
The anti‐inflammatory properties of transforming growth factor‐β(1) (TGF‐β(1)) account for its protection against atherosclerotic plaque rupture. This study investigates whether activation of the Nrf2 (nuclear factor erythroid 2 [NF‐E2]‐related factor 2) transcription pathway is involved in TGF‐β(1) mediated induction of the antioxidant enzyme heme oxygenase‐1 (HO‐1) in smooth muscle cells (SMC). Human aortic smooth muscle cells (HAoSMC) or wild‐type and Nrf2‐deficient mouse (MAoSMC) aortic SMC were treated with TGF‐β(1) (2.5–10 ng/ml, 0–24 hrs). We report the first evidence that TGF‐β(1) induces Nrf2 mediated HO‐1 expression and antioxidant response element activity, which was paralleled by enhanced superoxide production and expression of the NAD(P)H oxidase subunit p22(phox). TGF‐β(1) failed to induce HO‐1 expression in MAoSMC derived from Nrf2‐deficient mice, and HO‐1 induction by TGF‐β(1) in HAoSMC was attenuated by inhibition of extracellular signal regulated kinase or c‐jun‐N‐terminal kinase but not p38 mitogen activated protein kinase. Inhibition of NAD(P)H oxidase or scavenging of superoxide diminished HO‐1 induction in response to TGF‐β(1). The oxidative stress agents glucose oxidase (GOx) and diethylmaleate enhanced TGF‐β(1) generation and HO‐1 expression in HAoSMC, while antagonism of TGF‐β(1) signalling by adenoviral Smad7 overexpression attenuated their induction of HO‐1. Pre‐treatment of HAoSMC with TGF‐β(1) reduced nuclear translocation of the pro‐apoptotic mediator p53 elicited by GOx. Our findings demonstrate that Nrf2 is a new target of TGF‐β(1) signalling in the vasculature which may contribute to the atheroprotective properties attributed to this growth factor.